Effects of instrumental music as an auditory cues on Balance and functional mobility in patients With parkinson’s disease - TRUPTI SIDDAPUR; SHILPA KHANDARE; TUSHAR PALEKAR; MANISHA RATHI (International Journal of Pharma and Bio Sciences, 2017)
Parkinson’s disease (PD) is characterised by cardinal features of rigidity, tremors, bradykinesia & postural instability. Balance disturbances and gait alteration are common in Parkinson’s disease. It has been suggested that PD patients suffer from deficient internal cue production. 15 patients with age group 40-80 years were selected by convenient sampling. Intervention was given for balance and gait training by using external auditory cues thrice a week for 4 weeks. Pre and Post assessment was done before starting of 1st session and at the end of 12th session by using Timed Up and Go Scale (TUG), Berg Balance Scale (BBS) and cadence measurement. Statistical analysis was done by using Wilcoxon signed rank test. Significant improvement in pre and post scores of TUG (p=0.004), BBS (p=0.046) and cadence measurement (p=0.001) was observed. This study concludes that auditory cueing has shown significant improvement in overall evaluation of TUG score, BBS score and cadence measurement.